A survey on the challenges, limitations, and opportunities of online testing of infants and young children during the COVID-19 pandemic: using our experiences to improve future practices - Shore, Montana J.; Bukovsky, Danielle L.; Pinheiro, Sylvia G. V.; Hancock, Brendan M.; Liptrot, Emma M.; Kuhlmeier, Valerie A. (Frontiers in Psychology, 2023)
In developmental psychology, the widespread adoption of new methods for testing children does not typically occur over a matter of months. Yet, the COVID-19 pandemic and its associated social distancing requirements created a sudden need among many research groups to use a new method with which they had little or no experience: online testing. Here, we report results from a survey of 159 researchers detailing their early experiences with online testing. The survey approach allowed us to create a general picture of the challenges, limitations, and opportunities of online research, and it identified aspects of the methods that have the potential to impact interpretations of findings. We use the survey results to present considerations to improve online research practices.